Three- and four-jet final states in photoproduction at HERA - Chekanov, S; Derrick, M; Magill, S; Musgrave, B; Nicholass, D; Repond, J; Yoshida, R; Mattingly, M; Jechow, M; Pavel, N; Yagües Molina, A; Antonelli, S; et al. (2008)
Three- and four-jet final states have been measured in photoproduction at HERA using the ZEUS detector with an integrated luminosity of 121   pb -1. The results are presented for jets with transverse energy E Tjet > 6   GeV and pseudorapidity | η jet | < 2.4, in the kinematic region given by the virtuality of the photon Q 2 < 1   GeV 2 and the inelasticity 0.2 ≤ y ≤ 0.85 and in two mass regions defined as 25 ≤ M n j < 50   GeV and M n j ≥ 50   GeV, where M n j is the invariant mass of the n-jet system. The four-jet photoproduction cross section has been measured for the first time and represents the highest-order process studied at HERA. Both the three- and four-jet cross sections have been compared with leading-logarithmic parton-shower Monte Carlo models, with and without multi-parton interactions. The three-jet cross sections have been compared to an O (α α s2) perturbative QCD calculation. © 2007 Elsevier B.V. All rights reserved.